On the effects of tangential air inlets distribution configurations to the combustion characteristics of a direct injection liquid fueled Swirl Flameless Combustor (SFC). - K., Adam; A. Wahid, M. (2021)
Liquid fueled flameless combustion is a new niche in the energy-engineering department. The current trend on flameless combustion is mostly focused on gas fuel application due to the ease of achieving and maintaining flameless mode in the combustion process. The main purpose of this paper is to discuss the effects of evenly distributing tangential air inlets along the length of the combustion chamber of a Direct Injection Liquid Fueled Swirl Flameless Combustor (SFC) to the combustion characteristics in flameless mode. Ethyl alcohol or ethanol was used throughout the whole experiment. Only four tangential air inlets were used in this experiment for each configuration, whereas ethanol was directly injected axially. All 9 configurations were strategically divided into three categories; a) single inlet location, b) dual inlet locations, and c) triple inlet locations. The experiments were conducted at close to stoichiometry condition. The results showed that, although flameless mode was successfully achieved and stabilized at every configuration, it was also found that tangential air inlet configuration has a significant effect in the optimization and behavior of liquid fueled flameless combustion. The highest peak temperature was recorded by Configuration (G) at 800.45 oC, bur interestingly managed to produce the lowest value for the emission of CO and NOx gases, which were at 134 ppm and 0 ppm respectively. Thus, it was concluded that the best tangential air inlet configuration in this work was Configuration (G).